2022
DOI: 10.1021/acs.jpclett.2c02739
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-2D Ruddlesden–Popper Lead Halide Perovskites: How Edge Matters

Abstract: A band-mapping technique is introduced to investigate the formation of low‑energy edge states in quasi-2D Ruddlesden–Popper (RP) perovskites, (BA)2(MA) n−1Pb n I3n+1, through a localized mode of measurement, namely, scanning tunneling spectroscopy. The local band structures measured at different points reveal the formation of 3D CH3NH3PbI3 (MAPbI3) at the edges of the perovskite nanosheets; for thin films, the 3D phase (n = ∞) could be seen to form at grain boundaries. The presence of MAPbI3 at the edges or gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…20 Furthermore, the lower-energy edge states can be induced by external environments (e.g. moisture) or chemistry, leading to (i) the formation of a chemically induced new phase instead of a localized electronic state 21 and (ii) the formation of 3D perovskites on the edge of 2D RPPs 22,23 likely due to the loss of BA ligands and the resultant lattice shrinkage from 2D to 3D structures. 24,25 In contrast to the expectation that the edge states can effectively facilitate exciton dissociation into free charge carriers with long lifetime, Sun et al have recently reported that (i) highly efficient (480%) internal exciton dissociation is achievable in the 2D RPPs despite no photoluminescence signal from the lower-energy edge region and (ii) the collected exciton photoluminescence decays show identical kinetics at different locations with various distances to the edge states even in an exfoliated single crystal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Furthermore, the lower-energy edge states can be induced by external environments (e.g. moisture) or chemistry, leading to (i) the formation of a chemically induced new phase instead of a localized electronic state 21 and (ii) the formation of 3D perovskites on the edge of 2D RPPs 22,23 likely due to the loss of BA ligands and the resultant lattice shrinkage from 2D to 3D structures. 24,25 In contrast to the expectation that the edge states can effectively facilitate exciton dissociation into free charge carriers with long lifetime, Sun et al have recently reported that (i) highly efficient (480%) internal exciton dissociation is achievable in the 2D RPPs despite no photoluminescence signal from the lower-energy edge region and (ii) the collected exciton photoluminescence decays show identical kinetics at different locations with various distances to the edge states even in an exfoliated single crystal.…”
Section: Introductionmentioning
confidence: 99%
“…20 Furthermore, the lower-energy edge states can be induced by external environments ( e.g. moisture) or chemistry, leading to (i) the formation of a chemically induced new phase instead of a localized electronic state 21 and (ii) the formation of 3D perovskites on the edge of 2D RPPs 22,23 likely due to the loss of BA ligands and the resultant lattice shrinkage from 2D to 3D structures. 24,25…”
Section: Introductionmentioning
confidence: 99%
“…[27,31,36,[39][40][41] These interesting features of LES have invoked further experimental and theoretic investigations to understand the origin of LES and its control. [39][40][41][42][43][44][45][46][47][48][49][50] These LESs can experimentally be generated by exposing RPP to air, [33] UV-induced relaxation of terminal octahedra, [45] ablation through femtosecond pulse laser, [46] or through hydrostatic pressure. [40] Theoretical understanding falls into three ideas that are as such the electron-phonon coupling and structural deformation, [51] electron-phonon coupling-induced self-trapped exciton, [47,[52][53][54] or the polarized molecular alignment-induced internal electric-field theory [41] have been applied to explain the origin of LES; however, the understanding of the origin of LES is still not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…They aim at favoring a (111)/(101) crystal orientation to accelerate charge transport in quasi-2D RP perovskite devices. [10,11] Controlling the phase distribution and the growth direction of the perovskite layer is proposed as a promising strategy to enhance the charge transport of quasi-2D perovskites. [12] For example, Shao and co-workers introduced formamidinum (FA + ) cations to replace methylammonium (MA + ).…”
Section: Introductionmentioning
confidence: 99%